You can just use the quadratic equation. If you are solving a quadratic of the form ax^2 + bx + c = 0, the equation is:
x = [(-b) +- sqrt(b^2 - 4ac)]/2a
So in this case there are no complex roots (you have complex roots when b^2 -4ac < 0) so the roots are x = [-7 + - sqrt(49-4(4))]/2 = -(sqrt(33)+7)/4 and (sqrt(33)-7)/4... approximately -.63 and -6.4.
If you're doing this for your homework I hope you understand the explanation because you'll have to do it again on tests and such so just writing down this answer won't help. Good luck.
2007-01-18 01:31:38
·
answer #1
·
answered by ya_tusik 3
·
0⤊
0⤋
question huge kind a million : For this equation x^2 + 4*x + 7 = 0 , answer right here questions : A. come across the roots using Quadratic formula ! B. Use sprucing off the sq. to discover the concept of the equation ! answer huge kind a million : The equation x^2 + 4*x + 7 = 0 is already in a*x^2+b*x+c=0 form. through very reality the fee is already prepared in a*x^2+b*x+c=0 form, we get the fee of a = a million, b = 4, c = 7. 1A. come across the roots using Quadratic formula ! by using using abc formula the fee of x is both x1 = (-b+sqrt(b^2-4*a*c))/(2*a) and x2 = (-b-sqrt(b^2-4*a*c))/(2*a) We had be responsive to that a = a million, b = 4 and c = 7, lets favor to subtitute a,b,c interior the abc formula, with thos values. So x1 = (-(4) + sqrt( (4)^2 - 4 * (a million)*(7)))/(2*a million) and x2 = (-(4) - sqrt( (4)^2 - 4 * (a million)*(7)))/(2*a million) Which make x1 = ( -4 + sqrt( 16-28))/(2) and x2 = ( -4 - sqrt( 16-28))/(2) Which make x1 = ( -4 + sqrt( -12))/(2) and x2 = ( -4 - sqrt( -12))/(2) it truly is the similar with x1 = ( -4 + sqrt(12)*sqrt(-a million))/(2) and x2 = ( -4 - sqrt(12)*sqrt(-a million))/(2) thinking one and everyone be responsive to that sqrt(-a million) = i, So we get x1 = ( -4 + 3.46410161513775*i )/(2) and x2 = ( -4 - 3.46410161513775*i )/(2) We get following recommendations x1 = -2 + a million.73205080756888*i and x2 = -2 - a million.73205080756888*i 1B. Use sprucing off the sq. to discover the concept of the equation ! x^2 + 4*x + 7 = 0 ,divide both ingredient with a million Then we get x^2 + 4*x + 7 = 0 , And the coefficient of x is 4 lets favor to adhere to the undeniable fact that ( x + q )^2 = x^2 + 2*q*x + q^2 , and anticipate that q = 4/2 = 2 next, lets favor to split the consistent to form x^2 + 4*x + 4 + 3 = 0 And it really is the similar with ( x + 2 )^2 + 3 = 0 it truly is the similar with (( x + 2 ) - a million.73205080756888*i ) * (( x + 2 ) + a million.73205080756888*i ) = 0 by using starting up the brackets we are able to get ( x + 2 - a million.73205080756888*i ) * ( x + 2 + a million.73205080756888*i ) = 0 The recommendations are x1 = -2 + a million.73205080756888*i and x2 = -2 - a million.73205080756888*i
2016-11-25 01:10:11
·
answer #2
·
answered by sickels 4
·
0⤊
0⤋
dude!! just use the quadradic formula...
ax^2+bx+c=0 is the set up
this is the fromula...
x = (-b+or- (sq root of b^2 - 4ac)) / 2a
2007-01-18 01:29:28
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋